PENGEMBANGAN MEDIA POWER POINT INTERAKTIF PADA PEMBELAJARAN TEMATIK SISWA KELAS V - Trisniawati Trisniawati; Arina Aulia Niswatul Muniroh; Retno Utaminingsih (Perspektif Ilmu Pendidikan, 2021)
This research aimed to produced an interactive powerpoint as the proper media in thematic learning process for five graders. Proper means this research able to produce a product that can be used in the thematic learning process for five graders. The resulting product aimed to make a flexible learning media. This research was a kind of research and development based on the model developed by Borg and Gall. This research was done by steps: preliminary studies, planning, development of draft media product, validation, one on one trials, small group trials, revision II. The developed media was validated by a material expert and a media expert before conducted direct trials at school. Subject of this research was SD N Trenten 2, Candimulyo, Magelang Regency, Jawa Tengah. The trials were conducted to a teacher for one on one trials, and to four students for the small group trials. Instruments used to collect data were unstructured observation, unstructured interview, and questionnaire (material expert validation, media expert validation, and product trial questionnaire). The result of this research shows that material expert validation gets 4,38 belongs to the very good category. The result of media expert validation gets 3,56 belongs to the good category. The result of one on one trials gets 4,17 belongs to the good category. The result of small group trials gets 4,23 belongs to the very good category. Based on those results, thematic learning interactive powerpoint which is packaged in the form of an interactive CD proper to be used in the subtheme 1 theme 5 thematic learning process for five graders